Venous Thromboembolism Risk Assessment Models in Obstetrics: A Review of Current Practices and Future Directions - Francis, Antonia P.; Alshowaikh, Khadija; Napoleon, Melissa; Al-Khan, Abdulla; Kayaalp, Emre (American Journal of Perinatology, 2022)
Pregnancy is a major risk factor for venous thromboembolism (VTE) and its associated complications. The hypercoagulable state in both the antenatal and postnatal periods contributes to thromboembolism and continues to be a leading cause of maternal morbidity and mortality worldwide. The non-specific signs and symptoms of VTE in pregnancy and the lack of specific Risk Assessment Models (RAMs) propose a diagnostic challenge in the obstetric population. This review aims to discuss and compare existing RAMs and highlights the important challenges of using established RAMs in obstetric patients. It also emphasizes the importance of enhancing and individualizing RAMs in obstetrics to improve maternal healthcare.Key Points
Keywords: venous thromboembolism; pulmonary embolism; risk assessment model; pregnancy